THE MEDIATING EFFECT OF FINANCIAL TECHNOLOGY USAGE ON THE INFLUENCE OF FINANCIAL LITERACY ON THE FINANCIAL BEHAVIOR OF GEN Z IN SURABAYA - Sulistijono, Nur Ainina; Khusnah, Hidayatul (Jurnal Bisnis dan Keuangan, 2025)
The rapid advancement of digitalization and the growing use of financial technology have created an urgent need for younger generations to possess adequate financial literacy to manage financial resources effectively. However, previous studies have shown inconsistent findings regarding the relationship between financial literacy, financial technology, and financial behavior, indicating a gap that requires deeper examination, particularly among Generation Z in urban settings. To address this gap, this study examines the mediating effect of financial technology on the relationship between financial literacy and financial behavior among Generation Z in Surabaya. The population comprises Gen Z individuals born between 1997 and 2012 residing in Surabaya, and a sample of 400 respondents was selected using purposive sampling with the Lemeshow formula. Data were collected using an online questionnaire distributed via Google Forms and analyzed using WarpPLS 8.0. The results reveal that financial literacy has a positive and significant influence on financial behavior and also significantly affects the use of financial technology; additionally, financial technology positively and significantly influences financial behavior and mediates the relationship between financial literacy and financial behavior. These findings contribute to the literature by clarifying the mediating role of financial technology and addressing inconsistencies reported in previous studies, while offering practical insights for educational institutions, fintech providers, and regulators on developing strategies to enhance financial literacy, promote optimal fintech use, and strengthen financial inclusion among Generation Z.